Eupalinolide B inhibits periodontitis development by targeting ubiquitin conjugating enzyme UBE2D3 - Wenhua Kuang; Ruishen Zhuge; Ping Song; Letai Yi; Shujie Zhang; Ying Zhang; Yin Kwan Wong; Ruixing Chen; Junzhe Zhang; Yuanbo Wang; Dandan Liu; Zipeng Gong; et al. (MedComm)
Abstract Periodontitis is a chronic periodontal inflammatory disease caused by periodontal pathogens commonly seen in adults. Eupalinolide B (EB) is a sesquiterpenoid natural product extracted from Eupatorium lindleyanum and has been reported as a potential drug for cancers and immune disorders. Here, we explored the ameliorative effects and underlying molecular mechanism of EB on periodontitis for the first time. We demonstrated that EB ameliorates periodontal inflammation and alveolar bone resorption with a ligated periodontitis mouse model. In addition, the impact of EB on macrophages inflammation was examined in the Raw264.7 cell line. We identified ubiquitin‐conjugating enzyme, UBE2D3, as the direct covalent binding protein targets of EB by using a chemoproteomic method based on activity‐based protein profiling, biolayer interferometry method, and cellular thermal shift assay. Furthermore, the direct binding site of EB to UBE2D3 was identified using high‐resolution mass spectrometry and confirmed by experiments. Taken together, EB ameliorates periodontitis by targeting UBE2D3 to suppress the ubiquitination degradation of IκBα, leading to inactivation of nuclear transcription factor‐κB signaling pathway. And this was confirmed by siRNA‐mediated gene knockdown in inflammatory macrophages. Our results suggested that EB may be a new kind of UBE2D3 inhibitor and may become a promising therapeutic agent for anti‐periodontitis.